The ETS transcription factor GABPA inhibits bladder cancer aggressiveness by repressing extracellular matrix deposition and mechanotransduction signaling - Mingkai Dai; Xiaotian Yuan; Chenxi Sun; Runyuan Han; Magnus Björkholm; Feng Kong; Shengtian Zhao; Dawei Xu (Cell Death and Disease)
Abstract The ETS transcription factor GABPA exhibits an oncogenic effect by activating telomerase in many cancers; however, some studies imply its tumor suppressive activities. It is thus important to define its different roles in oncogenesis. By examining GABPA-transgenic mice, we unexpectedly observed that Collagen I and III (Col I and III) contents were significantly reduced in murine dermis, which was accompanied by downregulation of prolyl 4-hydroxylase (P4HA2), an enzyme catalyzing collagen folding and fiber stabilization. In bladder cancer (BC) cells, GABPA similarly inhibited Col I and III formation, whereas Col levels increased upon GABPA depletion, revealing its modulation of extracellular matrix (ECM) deposition and stiffness. Mechanistically, GABPA induced miR-30e expression by stimulating DICER1 transcription, and higher levels of miR-30e consequently targeted P4HA2 for its downregulation. Consistently, P4HA2 overexpression promoted Col formation, cell proliferation, and invasion, while its depletion or the specific P4HA2 inhibitor exerted opposite effects. In tumors derived from GABPA-overexpressed BC cells, atomic force microscope assessment showed that ECM rigidity was significantly reduced, coupled with diminished metastasis in xenografted mice, while P4HA2 overexpression led to stiffer ECM and increased metastasis, counteracting the GABPA effect. Moreover, GABPA knockdown or P4HA2 overexpression promoted YAP1 expression and its nuclear translocation, activating mechanotransduction signaling, through which accelerated proliferation and epithelial-mesenchymal transition occurred. Consistently, high miR-30e and P4HA2 expression were associated with favorable and unfavorable outcomes in BC patients, respectively. Collectively, GABPA inhibits P4HA2 expression and Col formation through the DICER1-miR30e axis, thereby repressing ECM deposition/stiffness and blocking mechanotransduction signaling, which consequently restrains BC aggressiveness. These findings unravel a novel role for GABPA in BC pathogenesis and have biological and therapeutic implications.